Analisis Beberapa Motif Pembelian Berdasarkan Karakteristik Produk Bordir Hasil Sentra Industri Kecil Di Kabupaten Sidoarjo Propinsi Jawa Timur - Jun Surjanti (EKUITAS (Jurnal Ekonomi dan Keuangan), 2006)
This study is dedicated to expand embroidery product of small scale industry at Sidoarjo. The objective is to analyze the effect of buying motives based on embroidery product characteristic, such as price, design, style, color mixture, art value, result, quality and phisical appearance, toward its buying frequency.Based on study at Desa Kedensari and Desa Kludan Kecamatan Tanggulangin found that the 288 respondent, that included housewife, women workers, and young adult segment, state that price, design, color mixture, art value, result and quality effect the embroidery buying frequency. Price is the foremost characteristic that effect buying frequency.This study refuse the first hypothesis, that is price, design, style, color mixture, art value, result, quality and phisical appearance do not effect buying frequency concurrently. The stepwise test explain that (1) price, design, style, color mixture, art value, result, quality and phisical apearance effect the buying frequency for all respondents both separately and concurrently. Determination coefficient (R Squared) is 0,7341, means independent variable contribute to dependent variable as 73,41% and the 26,29% rest is from other independent variables. (2) Price is the foremost variable that effect buying frequency of embroidery product. Its contribution is 15,45%..